The Role of Nigerian Translators in Promoting Nationhood and National Consciousness - Iteogu, Odizuru (NIU Journal of Social Sciences, 2019)
Language is doubly regarded in this paper as a psycho-social phenomenon relevant to every national development. It is in this context that this write-up has tried to examine the language question in Nigeria and how intellectual leadership through translators can contribute to the resolution of the raging controversy over selecting or creating a lingua franca for Nigeria’s multi-ethnic society. Sofar, Nigeria has made attempts, sometimes feeble or distorted, to devise an indigenously derived lingua franca. Three (3) national languages (Hausa, Igbo, Yoruba) out of five hundred and twenty two (522) local languages were selected with the intention of eventual selection of one of them as an interim measure to promote nationhood and national consciousness. Despite protests by minority groups and GUOSA language experiment, not much progress seems to have been made to several logistic and political factors. In the interim, academic and professional translators registered with the Nigerian Institute of Translators and interpreters (NITI) should be co-opted to provide intellectual leadership by translating major works of Nigerian major languages. This will surely promote intercultural understanding among Nigerians, perhaps reducing the mutual suspicion of ethic dominance among the major groups. The 21 st century should witness more concerted efforts towards a resolution of the language question and building a strong foundation for nationhood and national consciousness. Language is a major vehicle of transmission of cultural ideas, values and belief and a tool to stabilize or destabilize any political arrangements, especially in potentially unstable emerging democracies of the so-called third world nations of Africa. Keywords: Issues, Nigerian Languages, Role, Translators, Nationhood, National Consciousness.